2021
DOI: 10.1051/0004-6361/202141584
|View full text |Cite
|
Sign up to set email alerts
|

SWEET-Cat 2.0: The Cat just got SWEETer

Abstract: Aims. The catalog of Stars With ExoplanETs (SWEET-Cat) was originally introduced in 2013. Since then many more exoplanets have been confirmed, increasing significantly the number of host stars listed there. A crucial step toward a comprehensive understanding of these new worlds is the precise and homogeneous characterization of their host stars. Better spectroscopic stellar parameters along with new results from Gaia eDR3 provide updated and precise parameters for the discovered planets. A new version of the c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
46
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 71 publications
2
46
0
Order By: Relevance
“…We are able to reproduce the oxygen abundance reported in Kolecki & Wang (2021) using their photospheric stellar parameters, our equivalent width measurements, and 3D non-LTE abundance corrections from Amarsi et al (2019). We are therefore confident that the tension between our oxygen abundances results from the photospheric stellar parameters Kolecki & Wang (2021) derived for WASP-77 A that are hotter and more metal-poor than those derived by us, Maxted et al (2013), andMortier et al (2013) as updated by Sousa et al (2021).…”
Section: Elemental Abundancessupporting
confidence: 56%
See 1 more Smart Citation
“…We are able to reproduce the oxygen abundance reported in Kolecki & Wang (2021) using their photospheric stellar parameters, our equivalent width measurements, and 3D non-LTE abundance corrections from Amarsi et al (2019). We are therefore confident that the tension between our oxygen abundances results from the photospheric stellar parameters Kolecki & Wang (2021) derived for WASP-77 A that are hotter and more metal-poor than those derived by us, Maxted et al (2013), andMortier et al (2013) as updated by Sousa et al (2021).…”
Section: Elemental Abundancessupporting
confidence: 56%
“…found T eff = 5605 ± 41 K, log g = 4.37 ± 0.09, [Fe/H] = 0.07 ± 0.03, and M * = 0.96 ± 0.07 M . Updated parameters from the same group presented inSousa et al (2021) found T eff = 5595 ± 16 K, log g = 4.41 ± 0.03, [Fe/H] = 0.01 ± 0.01, and M * = 0.915 ± 0.004 M Kolecki & Wang (2021). found T eff = 5660 ± 30 K, log g = 4.49 ± 0.01, and [Fe/H] = −0.15 ± 0.06.…”
mentioning
confidence: 99%
“…For the Northern targets, we used HARPS-N. at TNG (Cosentino et al 2012) for the brightest targets (V<12.5), complementing it with PEPSI at LBT (Strassmeier et al 2003) for fainter targets. Brucalassi et al (2021) The sample presented in B21 was produced by cross-matching the Ariel Reference Sample with the spectra available in the 2020 version of SWEET-Cat (Stars With ExoplanETs Catalogue 2 ), and by selecting all targets in common with parameters' source "flag=1", which are the stars analysed homogeneously (see Santos et al 2013;Sousa et al 2021). The aim of B21 was to re-determine the stellar parameters of the Ariel-SWEET-Cat cross-matched sub-sample using two different methods (FAMA, Fast Automatic MOOG Analysis, Magrini et al 2013), based on the equivalent width, and FASMA (Fast Analysis of Spectra Made Automatically, Tsantaki et al 2018), based on spectral synthesis, and to compare them with the original results of SWEET-Cat.…”
Section: The Samplesmentioning
confidence: 99%
“…scaled to that of the star (close to the solar value at [Fe/H] = 0.04 ± 0.01;Sousa et al 2021). This yielded the input elemental abundances of carbon, oxygen, and nitrogen: C/H = 2.69 × 10 −4 , O/H = 5.37 × 10 −4 , and N/H = 7.41 × Article number, page 3 of 9 A&A proofs: manuscript no.…”
mentioning
confidence: 92%